The influence of regional minimum wages on unemployment rates in Indonesia: Multiple linear regression analysis - Ramadan, Aditya; Teguh, Ageng; Roselina, Antonia; Andriastuti, Luthfia; Antriyandarti, Ernoiz (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: This study investigates the influence of regional minimum wages (RMW), gross domestic product (GDP), and inflation on Indonesia's unemployment rates from 2012 to 2020. Methods: Multiple linear regression analysis examines the relationships between these economic variables. Findings: The findings reveal that RMW significantly negatively affects unemployment rates, indicating that a 1% increase in the minimum wage leads to a 3.951% decrease in unemployment, ceteris paribus. GDP also exhibits a significant negative influence, aligning with Okun's law, which suggests an inverse relationship between economic growth and unemployment. In contrast, inflation does not significantly impact unemployment rates during the studied period. Collectively, the three variables positively and significantly affect Indonesia's unemployment rate, with an adjusted R-squared value of 0.749. This implies that 74.9% of the variation in unemployment can be explained by GDP, inflation, and minimum wages, while other factors account for the remaining 25.1%. Conclusion: The study highlights the complex interplay between these macroeconomic indicators and unemployment, providing insights for policymakers to develop effective strategies for managing employment challenges in Indonesia. Novelty/Originality of this article: This empirical analysis reveals the dynamic relationship between RMW, GDP, inflation, and unemployment in Indonesia (2012—2020). The findings provide an evidence-based basis for formulating more effective and responsive employment and economic policies for Indonesia's labour market conditions.